Codeswitching as a scaffolding technique in teaching and learning: the case of Raffles International College (RIC) / Sh. Fei'ziah Syed Mohd Feisal Alqudsy - Syed Mohd Feisal Alqudsy, Sh. Fei'ziah (2010)
This thesis focuses on the perspectives of teachers and students on codeswitching as a teaching-learning technique outside of classroom contexts in Raffles International College (RIC), a private college in the heart of Kuala Lumpur, Malaysia. Despite having English as its medium of instruction, the teachers and students, especially those with spoken ability in English, Malay and Chinese, often practice codeswitching, which serves many functions in conversations (Auer, 1998; as cited in Riehl, 2005). This paper examines the attitudes of teachers and students to codeswitching in RIC, and the teachers’ and students’ perceptions of codeswitching as a teaching and learning strategy. Data was collected through nonparticipant observation, likert-type questionnaire, and short interview sessions. The participants of the study were 28 teachers and 85 students. In addition to that, three teachers were purposively selected for conversation observations and interview sessions. It was found that codeswitching is natural, acceptable and inevitable in the context of RIC, that the teachers and students generally have positive attitudes to codeswitching, and the teachers and students have mixed perception of codeswitching as teaching and learning strategy, as well as a gap of expectation towards the practice of codeswitching in the contexts of the college. From the findings of this research, the researcher identified that codeswitching is used as a technique to scaffold the teaching-learning of teachers and students of RIC. In conclusion, despite previous researches’ findings on codeswitching as a speech style, it is still considered as a strategy for the teachers and students of RIC outside of classroom contexts to communicate and achieve their teaching-learning goals.